E-135 Mechanical thrombectomy for small and medium vessel occlusion: a rural experience. (22nd July 2019) - Hopkins, N; Miller, V; Manchak, M; Drofa, A; Sachdeva, G; Kouznetsov, E
Abstract : Recent clinical trials have established that treatment of acute ischemic stroke secondary to large vessel occlusion with mechanical thrombectomy leads to improved revascularization and functional outcomes. Thus, the guidelines in treatment of ischemic stroke have been updated to reflect the results found in current literature. However, thrombectomy of small and medium vessel occlusions are a more controversial topic. The aim of the present study is to evaluate the outcomes of patients treated with mechanical thrombectomy for acute ischemic stroke secondary to more distal vessel occlusion and to highlight process times and outcomes in a center that receives patients from rural and underserved areas. We retrospectively reviewed the electronic medical record of 38 patients admitted to Sanford Health Cerebrovascular Service in Fargo, ND between March 2015 and May 2017 who underwent endovascular intervention for acute ischemic stroke secondary to a small caliber vessel occlusion. An average change in National Institutes of Health Stroke Scale (NIHSS) score of 4.94 was observed after intervention with mechanical thrombectomy with 26.31% of patients having a decrease in NIHSS of 10 or more and 36.84% of patients having a reduction of 6 or more. Successful recanalization was achieved in 94.74% of cases. Given the high rates of revascularization and significant reductions in NIHSS scores, mechanical thrombectomy may be reasonably extended to patients with occlusion of smaller, more distal vessels. Disclosures: N. Hopkins: None. V. Miller: None. M. Manchak: None. A. Drofa: 2; C; Medtronic, MicroVention. G. Sachdeva: None. E. Kouznetsov: None.